(untitled) (Journal of the College of Basic Education, 2022)
A biological experiment was carried out during the winter season 2010-2011 in the greenhouse of the Department of Life Sciences / College of Education for Pure Sciences / University of Baghdad, in order to determine the response of fenugreek plant to some foliar treatments with mineral elements (nitrogen and zinc) and its effect on the content of some elements, especially Mg, Ca, K , P, N and carbohydrate concentration. The experiment included a study of the effect of three concentrations of each nitrogen fertilizer, 0.1000.2000 mg/L, and zinc sulphate fertilizer 0.25.50 mg/L within the global experiment system according to the randomized complete block design with three replications.